One animal among many: Veterinarians in the global community - Waltner-Toews, David (1989)
Evidence from chemistry, physics, the biological sciences and the earth sciences is now accumulating that the earth functions as a living organism, with all the implications of circulatory and homeostatic systems which that implies. As veterinarians, we are more than simply handmaidens to agribusiness, the academic, pet and food industries, or government regulatory agencies. While our jobs may be specific, dependent, and circumscribed, our vocation can be nothing less than the health-care of all animal life — and hence by direct implication, the care of the earth, as a living organism, itself.